AKUNTABILITAS PELAYANAN PUBLIK DALAM PROGRAM E-KTP DI TINGKAT PEMERINTAHAN DAERAH PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MALANG - Desi Agitia (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: The purpose of this study was to determine the accountability of public services in the E-KTP program at the regional government level at the Malang Regency Population and Civil Registration Service, supporting factors and inhibitors. This study uses qualitative methods, with sampling techniques using purposive sampling. Data collection techniques are: interviews, observation, and documentation. Data analysis through the stages of reduction, presentation, and conclusion. The validity test uses technical triangulation. The results of the study prove that the accountability of public services in the E-KTP program at the Regional Government level at the Malang Regency Population and Civil Registration Service is good because it is in accordance with Service Operational Standards and is associated with public service standards such as procedures, time, costs, products, facilities and infrastructure. In the accountability of public services given to the community has been in line with the expectations of the community. This is supported by good official awareness, clear rules, healthy organizations, and good systems. On the other hand, there are inhibiting factors that must be dealt with, including the public not yet fully aware of the website and lack of knowledge about IT (information and technology) Dispendukcapil Malang Regency.Keywords: Accountability, Public ServicesAbstrak: Tujuan dari penelitian ini untuk mengetahui akuntabilitas pelayanan publik dalam program E-KTP di tingkat pemerintahan daerah pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Malang, faktor pendukung serta penghambatnya. Penelitian ini menggunakan metode kualitatif, dengan tehnik penentuan sampel menggunakan purposive sampling. Teknik pengumpulan data yaitu: wawancara, observasi, dan dokumentasi. Analisis data melalui tahap reduksi, penyajian, dan penarikan kesimpulan. Uji keabsahan menggunakan triangulasi teknik.Hasil penelitian membuktikan bahwa akuntabilitas pelayanan publik dalam program E-KTP di tingkat Pemerintahan Daerah pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Malang sudah baik karena sudah sesuai dengan Standar Operasional Pelayanan dan dikaitkan dengan standar pelayanan publik seperti prosedur, waktu, biaya, produk, sarana dan prasarana. Dalam akuntabilitas pelayanan publik yang diberikan pada masyarakat sudah sesuai harapan dari masyarakat. Hal tersebut didukung oleh kesadaran pejabat yang baik, aturan yang jelas, organisasi yang sehat, serta sistem yang baik. Di sisi lain, terdapat faktor penghambat yang harus ditangani diantaranya masyarakat belum sepenuhnya mengetahui website dan minimnya pengetahuan mengenai IT (informasi dan teknologi) Dispendukcapil Kabupaten Malang.Kata Kunci : Akuntabilitas, Pelayanan Publik